Complete Blood Count Abnormality in Acute Severe Asthma Patient Attending ED Compare to Stable Asthmatic Patient in Emergency Department - Rand Gaffer Malik Hassan; Ahmed Hussein Jasim (American Journal of Biomedicine and Pharmacy, 2026)
Asthma is a chronic inflammatory disorder of the airways characterize by variable airflow limitation and recurrent exacerbations. Inflammation plays a central role in its pathophysiology, making inhaled corticosteroids the cornerstone of long-term management. Despite advances in treatment, asthma remains a significant global health problem, affecting more than 300 million individuals worldwide. This study aimed to evaluate abnormalities in complete blood count (CBC) parameters in patients with acute severe asthma, compare these findings with stable asthmatic patients, and assess their association with disease severity. A comparative cross-sectional study was conducted on 100 asthmatic patients attending the emergency departments of Marjan Teaching Hospital and Al-Imam Al-Sadiq Hospital in Babylon, Iraq, between October 2025 and March 2026. Participants were divided into two groups: 50 patients with acute severe asthma and 50 patients with stable asthma. CBC parameters and pulmonary function tests (PFTs) were analyzed for all patients. The results demonstrated significant increases in white blood cell count, neutrophil count, neutrophil-to-lymphocyte ratio (NLR), and platelet count in patients with acute exacerbations compared to stable patients. Conversely, lymphocyte count and red blood cell count were significantly reduced. Pulmonary function parameters, including FVC, FEV1%, FEF 25–75%, and peak expiratory flow rate (PEFR), were markedly decreased in the acute exacerbation group. Regression analysis revealed that body mass index (BMI), platelet count, and mean platelet volume (MPV) were significant predictors of FEV1, while WBC was the only significant predictor of FEF 25–75%. In conclusion, acute severe asthma is associated with significant systemic inflammation and impaired lung function. CBC-derived indices, particularly NLR, may serve as simple, cost-effective biomarkers for assessing disease severity in emergency settings, especially in resource-limited healthcare systems.